Sir Cumference and the 100 percent goose chase : percentages : a math adventure - Neuschwander, Cindy (Charlesbridge, 2023)
"When Lady Di of Ameter and Percilla Centwell lose some of their geese on the way to deliver orders, they use percentages to make sure that everyone still gets their fair portion"--